PENGARUH PESAN KAMPANYE IKLAN LAYANAN MASYARAKAT SATGAS COVID-19 VERSI "INGAT PESAN IBU" DI TELEVISI TERHADAP SIKAP MENERAPKAN PROTOKOL KESEHATAN DI KECAMATAN TANAH SAREAL KOTA BOGOR - Muchamad Rifqi Fauzan Eka Nossa (2022)
The background of the increasing number of confirmed cases of COVID-19 in Indonesia has made the government not remain silent in dealing with this problem. Efforts are being made by the government to reduce the number of COVID-19 cases by forming a COVID-19 Task Force team that creates a "remember the mother's message" version of the COVID-19 Task Force public service advertising campaign together with the Rice band which is broadcast on several television stations containing appeals and an invitation to the public to apply health protocols in their daily activities. The purpose of the study was to find out how much influence the message of the COVID-19 task force public service advertising campaign "remember the mother's message" had on the attitude of implementing health protocols in Tanah Sareal District, Bogor City. The theory used is Attribution Theory. The method used is a quantitative method with the type of explanatory research. The location of this research is located in Tanah Sareal District, Bogor City with an age range of 15-50 years. The population in this study as many as 128,308 people with sampling using non-probability sampling and purposive sampling with the Taro Yamane formula and a sampling error rate of 5%, so that a sample of 400 respondents was obtained. To find out the relationship and influence between the two variables, the researcher used a correlation test with a result of 0.546 so that it had a strong correlation, a coefficient of determination test with an R Square value of 0.429 or there was an effect of exposure to the COVID-19 task force public service advertisement version of "remember the mother's message. "The attitude towards implementing health protocols in Tanah Sareal District, Bogor City is 42.9% and the significance value is 0.000 <0.05, so there is a significant difference. The results of this study were obtained through the t-test, where the tcount value was 17.305 < ttable value 1.96 so that from these results it was stated that H0 was rejected and H1 was accepted, it can be concluded that there was an effect of the COVID-19 Task Force public service advertising campaign "remember the message" version. mothers" on television regarding the attitude of implementing health protocols in Tanah Sareal District, Bogor City.